Perancangan Desain Kemasan Minuman Teh Untuk Meningkatkan Brand Awareness - Renzy Ayu Rohmatillah; Nabila Rahmi Oktaviani; Diana Setia Dewi (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Packaging has various functions such as protecting products from various causes of damage, as a medium for product communication and branding to consumers, maintaining products so that they last longer, and triggering consumer buying interest. The appearance of the packaging is one of the elements that can build brand identity and attract consumer attention. MSMEs "Waktunya Ngeteh" began to change its brand name and design new packaging to introduce its products to consumers and differentiate its brand image from competitors. There are two stages of the method used, namely the preparation stage and the creation stage. The preparation stage refers to the modern design method which includes three stages, namely identification, analysis, and synthesis. While the creation stage includes the pre-production, production and post-production stages. By implementing these stages, the resulting design can be in accordance with the design objectives. Packaging designed by implementing a design strategy that focuses on illustration can increase product brand awareness. The results of this study are a packaging design that is in accordance with the brand image, target audience and competitor factors of similar products.